Some problems in classification and diagnostics of soils in Russia - M. S. Simakova (Бюллетень Почвенного института им. В.В. Докучаева, 2016)
Under consideration are the history and principles of two soil classifications including “Classification and diagnostics of soils of the USSR” published in 1977 and “Russian soil classification system” of 2004. Their advantages and shortcomings are also considered. Special attention is paid to a new classification, in which not only natural but also the soils used in agriculture are classified for the first time. The soil classification published in 1977 elaborated on a basis of ecologic-genetic principles became out of date and was to be updated because of new knowledge on soils gained in the last years. New ideas determined the priority of substantive-genetic principle or more precisely the profile-genetic principles to be of major importance in the new classification system. A comprehensive analysis of ecological conditions for the soil development is absent. However, the agro-soils designed for cultivation of different agricultural crops can be recognized and typified only with account of ecological characteristics. The substantive-genetic approach to classify agricultural soils seems unacceptable because the most important diagnostic horizons become destructed in the course of soil tillage and the identical definitions or names of soils included into different types and even orders (agrozems) don’t provide the information on properties of initial soils. The classification must be elaborated using the principles permitting to determine and diagnose initial natural soils, thus maintaining their name, taxonomic level and indicating that they have been plowed. Not only the analysis of the soil profile but the analysis of soil-forming factors and the comparative-geographical method can be of great importance for these purposes. Only in this case the classification of agro-soils can be more informative to solve problems in agricultural production.